PTH-005 Does having a delayed transit time influence outcome in chronic constipation? - Khan, U; Kipling, M; Rowley-Conwy, D; Varma, J S; Yiannakou, Y (Gut, 2010)
IntroductionIt is a common practice to subclassify patients with chronic constipation (CC) as having slow or normal transit using radio-opaque marker studies. However, the procedure has never been validated for construct validity and shows poor responsiveness. Recent reports have shown no correlation with symptoms or quality of life1; there is no correlation between transit and faecal loading2; and little value in assessing segmental transit3. Even so, perhaps it would be valuable in predicting outcome. The aim of this study was to assess outcome in patients with CC who had undergone a transit study.MethodsThe case notes of consecutive follow-up patients attending a specialist constipation clinic were surveyed. Patients for the study group were selected on the basis of fulfilling the Rome III criteria for chronic constipation (FC or IBS-C) and having colonic transit measured at the first clinic assessment. This was done using a validated radio-opaque marker technique. Details of treatments were recorded together with demographic details. Patients were divided into two groups depending on the type of treatment required to stabilise symptoms (conservative=laxatives, biofeedback, rectal irrigation; surgical=SNS, rectocoele repair, ACE, stoma, colectomy). Paired student t-test was used to calculate the difference between the colonic transit times of the two groups. Subject were divided into patients with slow transit constipation (STC) (>45 markers retained) and normal transit constipation (NTC). The significance of treatments provided in each group was calculated using Fisher's exact test.Results148 patients were included, aged 18–72 years (mean 42.2 years). There were 22 men and 126 women. 79(53%) patients were satisfactorily managed with conservative treatment and 69 (46%) required surgical treatment. The mean transit time for conservative group was 56.13 h (SD 18.10) vs 55.14 h (SD18.32) for the surgical group. Paired t test did not demonstrate any differences between the transit times of the two groups (two-tailed p value 0.4761). There were 108 patients with STC and 40 with NTC. 53/108 (49%) had biofeedback in STC group whereas 16/40 (40%) in NTC group underwent biofeedback. There were no differences between STC and NTC groups (p value 0.3581).ConclusionThere is no evidence from these data that transit times influence outcome. The use of slow transit to determine therapy has never been proven and further work is required to justify the validity of subclassification based on transit.